2019
DOI: 10.15562/phpma.v7i2.222
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors for diarrhea among travellers visiting Bali

Abstract: Background and purpose: The number of foreign travellers visiting Bali continues to increase and diarrhea often occur among them. The purpose of this study is to determine the risk factors for the incidence of diarrhea in foreign travellers.Methods: A case control study was conducted in foreign travellers visiting the international clinic at the Port Health Office at Ngurah Rai International Airport in Denpasar during the period from May to October 2018. Cases were foreign travellers visiting the clinic with d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 10 publications
0
1
0
Order By: Relevance
“…The incidence of diarrhea in foreign tourists visiting Bali is 25.5%, from May to August 2013 [1]. One of the risk factors for diarrhea in travelers who come to Bali is consuming Balinese traditional food such as lawar, pork satay, and traditional barbecued pork [2].…”
Section: Introductionmentioning
confidence: 99%
“…The incidence of diarrhea in foreign tourists visiting Bali is 25.5%, from May to August 2013 [1]. One of the risk factors for diarrhea in travelers who come to Bali is consuming Balinese traditional food such as lawar, pork satay, and traditional barbecued pork [2].…”
Section: Introductionmentioning
confidence: 99%
“…(Luh Seri Ani, 2016) Another study found the incidence of diarrhea in foreign travelers was consumption of street food and traditional barbequed pork. (Ni Wayan Mega Sri Wahyuni, 2019) Bali is one of Indonesia's islands and a favorite tourist destination, especially for foreign tourists. The number of tourist visits increased again after the pandemic storm ended.…”
Section: Introductionmentioning
confidence: 99%